Foundations of the new test model for admission to the Universidad Nacional Mayor de San Marcos - Miljánovich Castilla, Manuel Asención (2005)
As a consequence of diverse studies the model’s test of admision to the San Marcos Mayor University that was in force since 1970 until 2005, has been modified substantially. The main innovations are: The setting of a first objective test of verbal and mathematics abilities with a qualifying character, and a second essay guideline test that measures associated know-how to development or compositional abilities, since the point of view of Learning cognitives theories.